(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
The article proposes a method that allows using the capabilities of neural networks to predict the tax base of the republic. This method is suitable for developing a positive short-term forecast. This forecast creates the possibility of making predictions in an intelligent mode, taking into account time series.